Peculiarities of Immidiate Postoperative Period in Abdominal Trauma With Splenic Injuries - V. V. Maslyakov; Y. G. Shapkin; A. Y. Dadayev; S. A. Kulikov; M. A. Shikhmagomedov (Неотложная медицинская помощь)
INTRODUCTION. Splenic injuries in abdominal trauma is one of the most common injuries in abdominal surgery. The damage to this organ occurs in 22.3–30%. This is the second most common injury among damages to parenchymal organs.AIM OF STUDY. To study the immediate results of treatment and to determine the factors that influence the choice of tactics for open injuries of the spleen.MATERIALS AND METHODS. The study included 75 patients with abdominal wound and damaged spleen. In 54 (72%) patients, stab and slash wounds were revealed, in 21 (28%) patients there were gunshot wounds (bullet or fragment). All patients were divided into two groups: Group A included 44 (58.6%) of patients, where the time gap between the time of injury and the surgery did not exceed 1 hour, and Group B, which included 31 (41.3 %) of cases, where the time gap between the moment of injury and surgical intervention exceeded 1 hour.RESULTS. As a result of the study, it was found that organ-preserving operations for open injuries of the spleen were possible in 33.3% of cases. The choice of surgical tactics for injuries of this organ depended on the type of damage to the organ: in case of gunshot wounds of the spleen, the organ-preserving operation was not possible at all, but this operation was performed for stab/slash wounds in 33.3% of cases. The development of complications and deaths directly depended on the journey time: in the case of that time gap up to one hour, complications developed in 27.3% of cases, and the mortality rate was 15.9%. If the time of journey exceeded 1 hour, the number of complications increased to 77.4%, and mortality rate grew up to 51.6%. According to our data, the number of complications and deaths depended more on the time of admission than on the type of operation performed. In addition, it is necessary to note one more factor that affected the lethal outcome and this was the type of the wound. Therefore, as a result of the study, it was found that mortality in the group with gunshot wounds amounted to 17 out of 21 (80.95%), and for stab/slash wounds it was 6 out of 54 (11.1%). It was found that the journey time and the type of operation performed operation affected the level of D-dimer in patients with splenic injuries. So, the level of D-dimer was 566±0.3 ng/ml in the group of the wounded, delivered within an hour after trauma, and 643±0.2 ng/ml in the group where the journey time exceeded an hour.CONCLUSIONS. 1. Performing organ-preserving operations with open injuries of the spleen is possible in 46.3% of cases and only for stab and slash wounds. Organ-preserving operations cannot be performed for gunshot wounds.2. The number of complications and deaths is more dependent on the journey time to the hospital than on the type of operation performed. If a patient is admitted within an hour after trauma, the complication rate is 27.3%, and mortality rate is 15.9%. If the journey time exceeds one hour, the complication rate is 77.4% and the mortality rate is 51.6%.3. In patients splenic inguries, the journey time and the type of the operation performed affect the level of the D-dimer, which may affect the course of the immediate postoperative period.